Pengaruh Biaya Dan Pendapatan Operasional Terhadap Profitabilitas Perusahaan (Study Kasus PT. Bosowa Mining) - Gisda, Ardy ansyah (JURNAL PABEAN : PERPAJAKAN BISNIS EKONOMI AKUNTANSI MANAJEMEN, 2025)
This study aimed to analyze the influence of Costs and Operating Income partialy as well as simultanously to profitability, the object of this research is PT. Mining domiciled company Bosowa Maros, South Sulawesi ProvinceThe research result through t test to examine partialy effect betwen cost and profitability obtained t value at point -4.683 with a significance value of 0.000 0.05. shows that costs have a negative and significant effect to Company profitability, and the value of t for operating income variable, showed the value of t at point 8.226 with a significance value of 0.000 0.05.its indicates that operating income had a positive and significant impact to Company profitabilityThe research result through F test to examine simultaneously effect betwen both of cost and operating income to company profitability through F test, obtained F value at point 35.382 with a significance value of 0,000 0.05 this result proves that the costs and operating income simultaneously significantly affected to the company profitability.The results showed that the coefficient of determination (Rsquare) obtained the value of R2 at point 0.682. This means that 68.2% Profitability affected by Costs and Operating Income and as much as 31.8% remaining that profitability are influenced by other variables which not examined in this study.